The whisperers - Connolly, John, 1968- (New York : Pockets Books, 2010)
On the border between Maine and Canada, a dangerous smuggling operation is taking place. Drugs, cash, weapons, even people-- and something ancient and powerful and evil...
The fictious character in this novel, Charlie'Bird' Parker, is not the same as the real Charlie'Bird' Parker the famous jazz musician.
Keywords: Parker, Charlie'Bird' (Fictitious character) -- Fiction; Private investigators -- Fiction; Smuggling -- Fiction